ANTESEDEN INTENSI ENTREPRENEURIAL DIGITAL PADA MAHASISWA UNIVERSITAS PADJADJARAN PADA MASA COVID-19 - Imam Suwandi; Sam'un Jaja Raharja; Margo Purnomo (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2020)
The purpose of this article is to find out how knowledge acquisition and entrepreneurial opportunity recognition can be antecedents of digital entrepreneurial intentions in students of the Faculty of Social and Political Sciences, Universitas Padjadjaran Class of 2019 and 2020. Sampling used a simple random sample with a total of 96 samples. The data analysis tool uses the Structural Equation Model. The results showed that knowledge acquisition and entrepreneurial opportunity recognition had a significant effect on digital entrepreneurial intentions. Likewise, knowledge acquisition has a significant effect on entrepreneurial opportunity recognition. The effect of knowledge acquisition mediated by entrepreneurial opportunity recognition on digital entrepreneurial intentions has a smaller significance than the direct effect of knowledge acquisition on digital entrepreneurial intentions. This study adds a digital context in the field of entrepreneurial intention so that it makes a new contribution to entrepreneurship research. This study provides recommendations for further studies, especially discussions of digital entrepreneurial intentions, which involve a larger population reach.  Tujuan dari artikel ini adalah untuk mengetahui bagaimana akuisisi pengetahuan dan pengenalan peluang entrepreneur dapat menjadi antesenden dari intensi entrepreneurial digital pada mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Padjadjaran Angkatan 2019 dan 2020. Sampling menggunakan simple random sampling dengan jumlah sebanyak 96 sampel.Alat analisis data memakai Structural Equation Model. Hasil penelitian memperlihatkan bahwa akuisisi pengetahuan dan pengenalan peluang entrepreneurial berpengaruh signifikan terhadap intensi entrepreneurial digital. Begitupun dengan akuisisi pengetahuan berpengaruh signifikan terhadap pengenalan peluang entrepreneurial. Penelitian ini menambahkan konteks digital dalam bidang entrepreneurial intention sehingga menambahkan kontribusi yang baru bagi penelitian entrepreneurship. Penelitian ini memberikan rekomendasi perlunya penelitianlebih lanjut khususnya pembahasan mengenai intensi entrepreneurial digital, yang melibatkan jangkauan populasi yang lebih besar.